Perancangan Aplikasi Data Mining Transaksi Penjualan untuk Mengetahui Pola Beli Konsumen pada Toko Singgalang Padang Menggunakan Algoritma Apriori Berbasis Web - Nelisa; Aulia Fitrul Hadi (Universitas Putra Indonesia YPTK Padang, 2018)
It takes a method or technique that can transform mountains of data into a valuable information or knowledge (knowledge) that are useful to support business decision making. Therefore in this paper association analysis application developed for extracting and interpreting the pattern of trend of sales of goods are often sold simultaneously from the transaction data using algorithms apriori. Apriori algorithms will from a frequent itemset as predetermined based on two parameters, support and confidence, to find the rules of the association between a combination of items. Knowledge of a product can be used by companies to increase production ansd sales of a product..